Agronomic performance and stability of Padjadjaran hybrid maize in different agroecosystems - Fadhillah, Farhan; Wicaksono, Fiky Yulianto; Yuwariah, Yuyun; Ruswandi, Dedi (Universitas Padjadjaran, 2025)
The development of high-yielding hybrid maize is a strategic step to address global food demand amidst climate change. This study evaluates the agronomic performance of 14 maize genotypes—10 newly developed F1 hybrids and 4 commercial checks—under two planting densities (95,000 and 55,000 plants/ha) across three agroecosystems (lowland, midland, and highland). The objectives were to identify superior and adaptive genotypes and analyze genotype × environment interactions using AMMI and GGE biplot methods. Genotype G12 exhibited the highest yield (338.4 g/plant) at high density, especially in the highland, but showed poor stability. In contrast, G5 demonstrated consistent performance and stability across environments. This study highlights G5’s potential for broad adaptation and provides insights for breeding programs targeting maize productivity in diverse agroecosystems.